Implementasi Nilai-Nilai Perenialisme dalam Membentuk Karakter Peserta Didik SDN Dewi Sartika - Suharyanto H. Soro; Maman Suherman; Ani Nurbaini; Arief Nur Afghan (LP. Ma'arif Janggan Magetan, 2024)
The role of perennialism values in developing the character of students at SDN Dewi Sartika is needed. Perennialism, as one of the educational philosophy schools, emphasizes the importance of universal and enduring values in shaping individuals with strong character. These values involve moral, ethical, and spiritual principles that are relevant across different eras. In the context of elementary education, the application of perennialism is considered essential for nurturing students who are not only academically competent but also possess integrity and robust morality. The aims of this study is to find out the perennialism values in building students character so they have a positive contribution for the Republic of Indonesia. This research employs a qualitative descriptive method with case study approach, Data collection methods including observation, interviews and document. The research subjects include various school elements, such as school participle, class teachers, students, and to provide a comprehensive perspective. The findings indicated that SDN Dewi Sartika has integrated perennialism values through various approaches. Teachers employ learning strategies based on deep discussions, moral reflections, and the use of classical texts rich in universal values. Furthermore, the school culture prioritizes discipline, responsibility, and mutual respect, which supports the character-building process of students. The implementation of the Merdeka Curriculum in this school also offers greater opportunities for teachers to design learning activities aligned with perennialism principles, both in terms of subject matter and non-academic activities.